Multi-approach carbon dioxide monitoring system for urban areas: test study from Kraków, Poland - Jasek-Kamińska, Alina; Sekuła, Piotr; Jagoda, Paweł; Skiba, Alicja; Bartyzel, Jakub; Chmura, Łukasz; Maslouski, Mikita; Gałkowski, Michał; Gorczyca, Zbigniew; Nęcki, Jarosław; et al. (Acta Geographica Lodziensia, 2024)
Urban areas contribute a significant uncertainty in carbon balance estimates, mainly due to spatial and temporal differences in emissions from distinct sources. A conglomerate carbon dioxide monitoring system for urban area was developed by Environmental Physics Group at the AGH University of Kraków. The system consists of 1) atmospheric CO2 concentration and isotopic composition measurements, 2) vertical profiles of CO2 combined with atmospheric transport modeling, and 3) direct measurements of CO2 flux to the atmosphere with eddy covariance. Utilizing various measurement methods allowed to obtain independent, complementary data on the CO2 sources and transport mechanisms in an urban area. The publication presents the pilot studies of the system conducted in Kraków in 2021.